A high-performance plastic particle production process
Patent Information
- Application Number
- CN202611034025.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-13
- Publication Date
- 2026-09-04
AI Technical Summary
[0004]为了解决现有技术中增韧与刚度难以平衡以及界面结合力弱的问题,本申请提供了一种高性能的塑胶颗粒的生产工艺,包括以下步骤:将再生聚丙烯、含有环氧基团的聚烯烃弹性体、经表面活化处理的纳米无机刚性粒子和α成核剂混合,得到预混料;将所述预混料进行熔融共混挤出,冷却切粒后得到塑胶颗粒
[0004] To address the challenges of balancing toughness and stiffness, as well as weak interfacial bonding in existing technologies, this application provides a production process for high-performance plastic granules, comprising the following steps: mixing recycled polypropylene, a polyolefin elastomer containing epoxy groups, surface-activated nano-inorganic rigid particles, and an α-nucleating agent to obtain a premix; and performing melt blending extrusion on the premix, followed by cooling and pelletizing to obtain plastic granules.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This application relates to the field of polymer material processing, specifically to a production process for high-performance plastic granules. Background Technology
[0002] Polypropylene (PP) is one of the world's most widely produced general-purpose plastics, with extensive applications in the automotive industry, home appliances, electronics, packaging, building materials, and furniture. With the advancement of the circular economy, the high-value utilization of recycled polypropylene (RPP) has become a focus of the industry. However, during mechanical recycling, the polymer is subjected to heat and high shear forces, leading to thermal oxidation and thermomechanical degradation. This degradation reduces the molecular weight of RPP, introduces polar terminal groups, and significantly degrades its mechanical properties, limiting its application in high-performance applications.
[0003] For RPP to replace virgin materials in automotive structural components, it must possess both high impact strength and sufficient stiffness. While traditional elastomer toughening methods can effectively improve impact strength, they significantly reduce tensile strength and flexural modulus. To compensate for the loss of stiffness, rigid fillers need to be added to the formulation. The core technological challenge for the high-value utilization of RPP lies in maintaining stiffness while increasing toughness, achieving a "stiffness-toughness balance." Summary of the Invention
[0004] To address the challenges of balancing toughness and stiffness, as well as weak interfacial bonding in existing technologies, this application provides a production process for high-performance plastic granules, comprising the following steps: mixing recycled polypropylene, a polyolefin elastomer containing epoxy groups, surface-activated nano-inorganic rigid particles, and an α-nucleating agent to obtain a premix; and performing melt blending extrusion on the premix, followed by cooling and pelletizing to obtain plastic granules.
[0005] During melt blending and extrusion, the polar terminal groups generated from the degradation of recycled polypropylene chemically react with the epoxy-containing polyolefin elastomer to form strong covalent bonds, achieving reactive compatibilization. This chemical bonding allows the elastomer to be stably dispersed in the matrix as submicron particles, undergoing cavitation and shear yielding upon impact, effectively absorbing impact energy. Simultaneously, surface-activated nano-inorganic rigid particles provide rigid support in the matrix, inducing crimping and shear yielding under external forces, producing a synergistic toughening and strengthening effect with the elastomer. The α-nucleating agent induces the formation of a thermodynamically stable α-crystal form, refining the spherulitic structure, improving the crystallinity and stiffness of the matrix, and avoiding the phase transformation risk of metastable crystal forms during secondary processing, resulting in higher performance stability.
[0006] Furthermore, the epoxy-containing polyolefin elastomer is a glycidyl methacrylate-grafted polyolefin elastomer, and the grafting rate of the glycidyl methacrylate is 0.5%-1wt%. Specific grafting rates can be selected as 0.5wt%, 0.8wt%, or 1.0wt%. The epoxy groups provided by GMA have high reactivity with carboxyl and hydroxyl groups. A grafting rate of 0.5%-1wt% can provide sufficient reaction sites to achieve adequate compatibilization, while avoiding excessive cross-linking and gel formation due to an excessively high grafting rate, which would affect processing flowability.
[0007] Furthermore, the surface-activated nano-inorganic rigid particles are stearic acid-activated nano-calcium carbonate with a particle size of 30-80 nm. Specific particle sizes can be selected as 30 nm, 40 nm, 50 nm, 60 nm, or 80 nm. Stearic acid activation reduces the surface energy of the nano-calcium carbonate to a level close to that of the polypropylene matrix, achieving good compatibility and uniform dispersion. The 30-80 nm particle size range allows it to effectively induce crazing and absorb energy while also limiting spherulite growth and refining the crystal structure.
[0008] Furthermore, the α-nucleating agent is an organophosphate nucleating agent. Specifically, the organophosphate nucleating agent can be selected from aryl phosphate nucleating agents such as NA-21. This type of nucleating agent has excellent dispersibility and nucleation efficiency, can significantly shorten the semi-crystallization time and improve crystallinity at extremely low addition levels, and is itself non-coloring, so it does not affect the color matching of plastic granules.
[0009] Furthermore, the manufacturing process also includes chopped glass fibers. The chopped glass fibers provide directional reinforcement in the matrix, effectively compensating for any modulus loss that may be caused by the introduction of elastomers, and further improving the tensile strength and flexural modulus of the plastic particles.
[0010] Furthermore, in the melt blending extrusion step, the chopped glass fibers are fed from the side feed port of the extruder. This side feeding method avoids the chopped glass fibers undergoing high shear in the early stages of extrusion, reducing excessive fiber breakage and ensuring the retained fiber length and reinforcing effect.
[0011] Further, based on 100 parts by weight of recycled polypropylene, the polyolefin elastomer containing epoxy groups comprises 5-15 parts, the surface-activated nano-inorganic rigid particles comprise 3-15 parts, and the α-nucleating agent comprises 0.2-0.3 parts. Specifically, the elastomer can be selected from 5 parts, 8 parts, 10 parts, 12 parts, or 15 parts; the rigid particles can be selected from 3 parts, 5 parts, 8 parts, 10 parts, 12 parts, or 15 parts; and the nucleating agent can be selected from 0.2 parts, 0.25 parts, 0.28 parts, or 0.3 parts. This proportion range allows the components to work synergistically to achieve a balance between rigidity and toughness.
[0012] Furthermore, based on 100 parts by weight of recycled polypropylene, the chopped glass fiber comprises 3-15 parts. Specifically, the chopped glass fiber can be selected as 3 parts, 5 parts, 8 parts, 10 parts, or 15 parts, adjusted according to different requirements for stiffness and toughness.
[0013] Furthermore, the melt blending extrusion temperature is 170-240℃. Within this temperature range, good melt plasticization of the polypropylene matrix can be ensured, as well as sufficient ring-opening reaction between the epoxy groups and polar end groups can be carried out, while avoiding excessively high temperatures that could lead to severe degradation of the polypropylene.
[0014] Furthermore, the process includes an injection molding step, where the diced plastic granules are injection molded at an injection temperature of 200-220°C and a mold temperature of 40-60°C. These molding conditions facilitate mold filling and maintain the stable crystalline structure of the α-crystal form, resulting in products with excellent overall mechanical properties. Detailed Implementation
[0015] To facilitate understanding of this application, a more complete description will be provided below. This application can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a more thorough and complete understanding of the disclosure of this application.
[0016] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of that feature. In the description of the application, "multiple" means at least two, such as two, three, etc., unless otherwise explicitly specified. In the description of this application, "several" means at least one, such as one, two, etc., unless otherwise explicitly specified.
[0017] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used herein is for the purpose of describing particular embodiments only and is not intended to be limiting of the application. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.
[0018] In this application, the technical features described in an open-ended manner include both closed technical solutions consisting of the listed features and open technical solutions that include the listed features.
[0019] In this application, numerical ranges are referred to as continuous unless otherwise specified, and include the minimum and maximum values of the range, as well as every value between the minimum and maximum values. Furthermore, when the range refers to integers, it includes every integer between the minimum and maximum values of the range. Additionally, when multiple ranges are provided to describe a feature or characteristic, the ranges may be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges to which they are incorporated.
[0020] In some preferred embodiments, the grafting rate of the epoxy group-containing polyolefin elastomer can be selected from any value among 0.5%, 0.6%, 0.8%, and 1.0%; and its amount can be selected from any value among 5 parts, 6 parts, 7 parts, 8 parts, 10 parts, 12 parts, or 15 parts.
[0021] In some preferred embodiments, the particle size of the surface-activated nano-inorganic rigid particles can be selected from any value of 30 nm, 40 nm, 50 nm, 60 nm or 80 nm; the amount can be selected from any value of 3 parts, 5 parts, 8 parts, 10 parts, 12 parts or 15 parts; the surface activating agent can be stearic acid, and the treatment amount can be 2 wt% or 3 wt%.
[0022] In some preferred embodiments, the amount of the α-nucleating agent can be selected from any value among 0.2 parts, 0.25 parts, 0.28 parts or 0.3 parts; specifically, it can be selected from organophosphate nucleating agents such as NA-21 or NA-11.
[0023] In some preferred embodiments, the amount of chopped glass fiber can be selected from any value of 3 parts, 5 parts, 8 parts or 15 parts; the diameter can be any value of 10 μm, 11 μm, 12 μm or 13 μm; and the length can be any value of 3 mm, 3.5 mm, 4 mm or 4.5 mm.
[0024] In some preferred embodiments, the temperature of the melt blending extrusion can be selected from any value among 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, or 240°C; and the screw speed can be selected from any value among 250 rpm, 280 rpm, 300 rpm, 320 rpm, or 350 rpm.
[0025] Example 1: This example provides a production process for high-performance plastic granules.
[0026] 100 parts of recycled polypropylene (MFR 20 g / 10min, 230℃ / 2.16kg, obtained from recycled household appliance materials); glycidyl methacrylate grafted polyolefin elastomer (GMA grafting rate 0.5 wt%, MFR 3.5 g / 10min, 190℃ / 2.16kg, density 0.88 g / cm³). 3 10 parts; 8 parts of nano-calcium carbonate (particle size 40 nm, stearic acid treatment amount 2.5 wt%) surface-activated with stearic acid; 5 parts of chopped glass fiber (diameter 12 μm, length 4 mm, surface-treated with aminosilane coupling agent KH-550); 0.2 parts of α-nucleating agent NA-21 (organophosphate aluminum salt, white powder); 0.2 parts of antioxidant 1010 (hindered phenolic primary antioxidant); 0.1 parts of antioxidant 168 (phosphite secondary antioxidant); 0.5 parts of zinc stearate (lubricant).
[0027] The preparation process includes the following steps: Step 1: Raw material pretreatment. The recycled polypropylene granules were dried in an 80℃ forced-air drying oven for 4 hours to achieve a moisture content of ≤0.05%; the nano-calcium carbonate treated with stearic acid surface activation was dried at 105℃ for 2 hours; and the chopped glass fibers were dried at 110℃ for 2 hours.
[0028] Step 2: Premixing. 100 parts of recycled polypropylene, 10 parts of glycidyl methacrylate-grafted polyolefin elastomer, 8 parts of stearic acid-surface-activated nano-calcium carbonate, 0.2 parts of α-nucleating agent NA-21, 0.2 parts of antioxidant 1010, 0.1 parts of antioxidant 168, and 0.5 parts of zinc stearate are mixed in a high-speed mixer at 700 rpm for 4 minutes to ensure uniform distribution of the components, thus obtaining a premix.
[0029] Step 3: Melt Blending Extrusion. A co-rotating twin-screw extruder (L / D ratio L / D = 40) was used. The screw temperatures for each zone were set as follows: Zone 1 170℃, Zone 2 185℃, Zone 3 200℃, Zone 4 210℃, Zone 5 215℃, Zone 6 215℃, Zone 7 210℃, Zone 8 205℃, and Die Head 200℃. The premix obtained in Step 2 was added through the main feed inlet, and the chopped glass fibers were added through the side feed inlets of zones 5-6. The screw speed was 300 rpm. After cooling in a water bath, the extruded strip was granulated. The granules were dried at 80℃ for 4 hours to obtain plastic granules.
[0030] Step 4: Injection molding. The dried plastic granules are injection molded into standard samples using an injection molding machine. The injection temperature is 220°C for all sections of the barrel, 40°C for the mold, 70 MPa for the injection pressure, 40 MPa for the holding pressure, and 20s for the cooling time.
[0031] Example 2: This example provides a production process for high-performance plastic granules.
[0032] 100 parts of recycled polypropylene (MFR 20 g / 10min, 230℃ / 2.16kg, obtained from recycled household appliance materials); glycidyl methacrylate grafted polyolefin elastomer (GMA grafting rate 0.5 wt%, MFR 3.5 g / 10min, 190℃ / 2.16kg, density 0.88 g / cm³). 3 15 parts; 10 parts of nano-calcium carbonate (particle size 40 nm, stearic acid treatment amount 2.5 wt%, activation index ≥95%) surface-activated by stearic acid; 8 parts of chopped glass fiber (diameter 12 μm, length 4 mm, surface-treated with aminosilane coupling agent KH-550); 0.2 parts of α-nucleating agent NA-21 (organophosphate aluminum salt, white powder); 0.2 parts of antioxidant 1010 (hindered phenolic primary antioxidant); 0.1 parts of antioxidant 168 (phosphite secondary antioxidant); 0.5 parts of zinc stearate (lubricant).
[0033] The preparation process includes the following steps: Step 1: Raw material pretreatment. The recycled polypropylene granules were dried in an 80℃ forced-air drying oven for 4 hours to achieve a moisture content of ≤0.05%; the nano-calcium carbonate treated with stearic acid surface activation was dried at 105℃ for 2 hours; and the chopped glass fibers were dried at 110℃ for 2 hours.
[0034] Step 2: Premixing. 100 parts of recycled polypropylene, 15 parts of glycidyl methacrylate-grafted polyolefin elastomer, 10 parts of stearic acid-surface-activated nano-calcium carbonate, 0.2 parts of α-nucleating agent NA-21, 0.2 parts of antioxidant 1010, 0.1 parts of antioxidant 168, and 0.5 parts of zinc stearate are mixed in a high-speed mixer at 700 rpm for 4 minutes to ensure uniform distribution of the components, thus obtaining a premix.
[0035] Step 3: Melt Blending Extrusion. A co-rotating twin-screw extruder (L / D ratio L / D = 40) was used. The screw temperatures for each zone were set as follows: Zone 1 170℃, Zone 2 185℃, Zone 3 200℃, Zone 4 210℃, Zone 5 215℃, Zone 6 215℃, Zone 7 210℃, Zone 8 205℃, and Die Head 200℃. The premix obtained in Step 2 was added through the main feed inlet, and the chopped glass fibers were added through the side feed inlets of zones 5-6. The screw speed was 300 rpm. After cooling in a water bath, the extruded strip was granulated. The granules were dried at 80℃ for 4 hours to obtain plastic granules.
[0036] Step 4: Injection molding. The dried plastic granules are injection molded into standard samples using an injection molding machine. The injection temperature is 220°C for all sections of the barrel, 40°C for the mold, 70 MPa for the injection pressure, 40 MPa for the holding pressure, and 20s for the cooling time.
[0037] Example 3: This example provides a production process for high-performance plastic granules.
[0038] 100 parts of recycled polypropylene (MFR 20 g / 10min, 230℃ / 2.16kg, obtained from recycled household appliance materials); glycidyl methacrylate grafted polyolefin elastomer (GMA grafting rate 0.5 wt%, MFR 3.5 g / 10min, 190℃ / 2.16kg, density 0.88 g / cm³). 3 6 parts; 12 parts of nano-calcium carbonate (particle size 40 nm, stearic acid treatment amount 2.5 wt%, activation index ≥95%) surface-activated by stearic acid; 3 parts of chopped glass fiber (diameter 12 μm, length 4 mm, surface-treated with aminosilane coupling agent KH-550); 0.3 parts of α-nucleating agent NA-21 (organophosphate aluminum salt, white powder); 0.2 parts of antioxidant 1010 (hindered phenolic main antioxidant); 0.1 parts of antioxidant 168 (phosphite secondary antioxidant); 0.5 parts of zinc stearate (lubricant).
[0039] The preparation process includes the following steps: Step 1: Raw material pretreatment. The recycled polypropylene granules were dried in an 80℃ forced-air drying oven for 4 hours to achieve a moisture content of ≤0.05%; the nano-calcium carbonate treated with stearic acid surface activation was dried at 105℃ for 2 hours; and the chopped glass fibers were dried at 110℃ for 2 hours.
[0040] Step 2: Premixing. 100 parts of recycled polypropylene, 6 parts of glycidyl methacrylate-grafted polyolefin elastomer, 12 parts of stearic acid-surface-activated nano-calcium carbonate, 0.3 parts of α-nucleating agent NA-21, 0.2 parts of antioxidant 1010, 0.1 parts of antioxidant 168, and 0.5 parts of zinc stearate are mixed in a high-speed mixer at 700 rpm for 4 minutes to ensure uniform distribution of the components, thus obtaining a premix.
[0041] Step 3: Melt Blending Extrusion. A co-rotating twin-screw extruder (L / D ratio L / D = 40) was used. The screw temperatures for each zone were set as follows: Zone 1 170℃, Zone 2 185℃, Zone 3 200℃, Zone 4 210℃, Zone 5 215℃, Zone 6 215℃, Zone 7 210℃, Zone 8 205℃, and Die Head 200℃. The premix obtained in Step 2 was added through the main feed inlet, and the chopped glass fibers were added through the side feed inlets of zones 5-6. The screw speed was 300 rpm. After cooling in a water bath, the extruded strip was granulated. The granules were dried at 80℃ for 4 hours to obtain plastic granules.
[0042] Step 4: Injection molding. The dried plastic granules are injection molded into standard samples using an injection molding machine. The injection temperature is 220°C for all sections of the barrel, 40°C for the mold, 70 MPa for the injection pressure, 40 MPa for the holding pressure, and 20s for the cooling time.
[0043] Example 4: This example provides a production process for high-performance plastic granules.
[0044] 100 parts of recycled polypropylene (MFR 20 g / 10min, 230℃ / 2.16kg, obtained from recycled household appliance materials); glycidyl methacrylate grafted polyolefin elastomer (GMA grafting rate 1.0 wt%, MFR 3.5 g / 10min, 190℃ / 2.16kg, density 0.88 g / cm³). 3 7 parts; 8 parts of nano-calcium carbonate (particle size 40 nm, stearic acid treatment amount 2.5 wt%, activation index ≥95%) surface-activated with stearic acid; 5 parts of chopped glass fiber (diameter 12 μm, length 4 mm, surface-treated with aminosilane coupling agent KH-550); 0.2 parts of α-nucleating agent NA-21 (organophosphate aluminum salt, white powder); 0.2 parts of antioxidant 1010 (hindered phenolic main antioxidant); 0.1 parts of antioxidant 168 (phosphite auxiliary antioxidant); 0.5 parts of zinc stearate (lubricant).
[0045] The preparation process includes the following steps: Step 1: Raw material pretreatment. The recycled polypropylene granules were dried in an 80℃ forced-air drying oven for 4 hours to achieve a moisture content of ≤0.05%; the nano-calcium carbonate treated with stearic acid surface activation was dried at 105℃ for 2 hours; and the chopped glass fibers were dried at 110℃ for 2 hours.
[0046] Step 2: Premixing. 100 parts of recycled polypropylene, 7 parts of glycidyl methacrylate-grafted polyolefin elastomer, 8 parts of stearic acid-surface-activated nano-calcium carbonate, 0.2 parts of α-nucleating agent NA-21, 0.2 parts of antioxidant 1010, 0.1 parts of antioxidant 168, and 0.5 parts of zinc stearate are mixed in a high-speed mixer at 700 rpm for 4 minutes to ensure uniform distribution of the components, thus obtaining a premix.
[0047] Step 3: Melt Blending Extrusion. A co-rotating twin-screw extruder (L / D ratio L / D = 40) was used. The screw temperatures for each zone were set as follows: Zone 1 170℃, Zone 2 185℃, Zone 3 200℃, Zone 4 210℃, Zone 5 215℃, Zone 6 215℃, Zone 7 210℃, Zone 8 205℃, and Die Head 200℃. The premix obtained in Step 2 was added through the main feed inlet, and the chopped glass fibers were added through the side feed inlets of zones 5-6. The screw speed was 300 rpm. After cooling in a water bath, the extruded strip was granulated. The granules were dried at 80℃ for 4 hours to obtain plastic granules.
[0048] Step 4: Injection molding. The dried plastic granules are injection molded into standard samples using an injection molding machine. The injection temperature is 220°C for all sections of the barrel, 40°C for the mold, 70 MPa for the injection pressure, 40 MPa for the holding pressure, and 20s for the cooling time.
[0049] Example 5: This example provides a production process for high-performance plastic granules.
[0050] 100 parts of recycled polypropylene (MFR 20 g / 10min, 230℃ / 2.16kg, obtained from recycled household appliance materials); glycidyl methacrylate grafted polyolefin elastomer (GMA grafting rate 0.5 wt%, MFR 3.5 g / 10min, 190℃ / 2.16kg, density 0.88 g / cm³). 3 10 parts; 15 parts of nano-calcium carbonate (particle size 40 nm, stearic acid treatment amount 2.5 wt%, activation index ≥95%) surface-activated by stearic acid; 0.2 parts of α-nucleating agent NA-21 (organoaluminum phosphate salt, white powder); 0.2 parts of antioxidant 1010 (hindered phenolic main antioxidant); 0.1 parts of antioxidant 168 (phosphite auxiliary antioxidant); 0.5 parts of zinc stearate (lubricant).
[0051] The preparation process includes the following steps: Step 1: Raw material pretreatment. The recycled polypropylene granules were dried in an 80℃ forced-air drying oven for 4 hours to achieve a moisture content of ≤0.05%; the nano-calcium carbonate that had undergone stearic acid surface activation treatment was dried at 105℃ for 2 hours.
[0052] Step 2: Premixing. 100 parts of recycled polypropylene, 10 parts of glycidyl methacrylate-grafted polyolefin elastomer, 15 parts of stearic acid-surface-activated nano-calcium carbonate, 0.2 parts of α-nucleating agent NA-21, 0.2 parts of antioxidant 1010, 0.1 parts of antioxidant 168, and 0.5 parts of zinc stearate are mixed in a high-speed mixer at 700 rpm for 4 minutes to ensure uniform distribution of the components, thus obtaining a premix.
[0053] Step 3: Melt Blending Extrusion. A co-rotating twin-screw extruder (L / D ratio L / D = 40) was used. The screw temperatures for each zone were set as follows: Zone 1 170℃, Zone 2 185℃, Zone 3 200℃, Zone 4 210℃, Zone 5 215℃, Zone 6 215℃, Zone 7 210℃, Zone 8 205℃, and Die Head 200℃. The premix obtained in Step 2 was added through the main feed inlet, and the screw speed was 300 rpm. The extruded strip was cooled in a water bath and then granulated. The granules were dried at 80℃ for 4 hours to obtain plastic granules.
[0054] Step 4: Injection molding. The dried plastic granules are injection molded into standard samples using an injection molding machine. The injection temperature is 220°C for all sections of the barrel, 40°C for the mold, 70 MPa for the injection pressure, 40 MPa for the holding pressure, and 20s for the cooling time.
[0055] Example 6: This example provides a production process for high-performance plastic granules.
[0056] 100 parts of recycled polypropylene (MFR 20 g / 10min, 230℃ / 2.16kg, obtained from recycled household appliance materials); glycidyl methacrylate grafted polyolefin elastomer (GMA grafting rate 0.5 wt%, MFR 3.5 g / 10min, 190℃ / 2.16kg, density 0.88 g / cm³). 3 10 parts; 4 parts of nano-calcium carbonate (particle size 40 nm, stearic acid treatment amount 2.5 wt%) surface-activated with stearic acid; 4 parts of nano-calcium carbonate (particle size 40 nm, KH-570 treatment amount 2.5 wt%) surface-treated with KH-570 vinyl silane coupling agent; 5 parts of chopped glass fiber (diameter 12 μm, length 4 mm, surface-treated with aminosilane coupling agent KH-550); 0.2 parts of α-nucleating agent NA-21 (organoaluminum phosphate salt, white powder); 0.2 parts of antioxidant 1010 (hindered phenolic primary antioxidant); 0.1 parts of antioxidant 168 (phosphite secondary antioxidant); 0.5 parts of zinc stearate (lubricant).
[0057] The preparation process includes the following steps: Step 1: Raw material pretreatment. The recycled polypropylene granules were dried in an 80℃ forced-air drying oven for 4 hours to achieve a moisture content of ≤0.05%; the nano-calcium carbonate treated with stearic acid surface activation was dried at 105℃ for 2 hours; and the chopped glass fibers were dried at 110℃ for 2 hours.
[0058] Step 2: Premixing. 100 parts of recycled polypropylene, 10 parts of glycidyl methacrylate-grafted polyolefin elastomer, 8 parts of two types of nano-calcium carbonate, 0.2 parts of α-nucleating agent NA-21, 0.2 parts of antioxidant 1010, 0.1 parts of antioxidant 168, and 0.5 parts of zinc stearate are mixed in a high-speed mixer at 700 rpm for 4 minutes to ensure uniform distribution of the components, thus obtaining a premix.
[0059] Step 3: Melt Blending Extrusion. A co-rotating twin-screw extruder (L / D ratio L / D = 40) was used. The screw temperatures for each zone were set as follows: Zone 1 170℃, Zone 2 185℃, Zone 3 200℃, Zone 4 210℃, Zone 5 215℃, Zone 6 215℃, Zone 7 210℃, Zone 8 205℃, and Die Head 200℃. The premix obtained in Step 2 was added through the main feed inlet, and the chopped glass fibers were added through the side feed inlets of zones 5-6. The screw speed was 300 rpm. After cooling in a water bath, the extruded strip was granulated. The granules were dried at 80℃ for 4 hours to obtain plastic granules.
[0060] Step 4: Injection molding. The dried plastic granules are injection molded into standard samples using an injection molding machine. The injection temperature is 220°C for all sections of the barrel, 40°C for the mold, 70 MPa for the injection pressure, 40 MPa for the holding pressure, and 20s for the cooling time.
[0061] Comparative Example 1: This comparative example provides a production process for plastic granules. The difference from Example 1 is that this comparative example uses ungrafted ordinary polyolefin elastomer instead of glycidyl methacrylate-grafted polyolefin elastomer.
[0062] 100 parts of recycled polypropylene (MFR 20 g / 10min, 230℃ / 2.16kg, obtained from recycled household appliance materials); ordinary polyolefin elastomer (density 0.88 g / cm³). 3 10 parts of the following: MFR 3.5 g / 10min, 190℃ / 2.16kg; 8 parts of nano-calcium carbonate (particle size 40 nm, stearic acid treatment amount 2.5 wt%, activation index ≥95%) surface-activated with stearic acid; 5 parts of short-cut glass fiber (diameter 12μm, length 4 mm, surface-treated with aminosilane coupling agent KH-550); 0.2 parts of α-nucleating agent NA-21 (organoaluminum phosphate salt, white powder); 0.2 parts of antioxidant 1010 (hindered phenolic primary antioxidant); 0.1 parts of antioxidant 168 (phosphite secondary antioxidant); and 0.5 parts of zinc stearate (lubricant).
[0063] The preparation process includes the following steps: Step 1: Raw material pretreatment. The recycled polypropylene granules were dried in an 80℃ forced-air drying oven for 4 hours to achieve a moisture content of ≤0.05%; the nano-calcium carbonate treated with stearic acid surface activation was dried at 105℃ for 2 hours; and the chopped glass fibers were dried at 110℃ for 2 hours.
[0064] Step 2: Premixing. 100 parts of recycled polypropylene, 10 parts of ordinary polyolefin elastomer, 8 parts of nano-calcium carbonate treated with stearic acid surface activation, 0.2 parts of α-nucleating agent NA-21, 0.2 parts of antioxidant 1010, 0.1 parts of antioxidant 168, and 0.5 parts of zinc stearate are mixed in a high-speed mixer at 700 rpm for 4 minutes to ensure uniform distribution of the components, thus obtaining a premix.
[0065] Step 3: Melt Blending Extrusion. A co-rotating twin-screw extruder (L / D ratio L / D = 40) was used. The screw temperatures for each zone were set as follows: Zone 1 170℃, Zone 2 185℃, Zone 3 200℃, Zone 4 210℃, Zone 5 215℃, Zone 6 215℃, Zone 7 210℃, Zone 8 205℃, and Die Head 200℃. The premix obtained in Step 2 was added through the main feed inlet, and the chopped glass fibers were added through the side feed inlets of zones 5-6. The screw speed was 300 rpm. After cooling in a water bath, the extruded strip was granulated. The granules were dried at 80℃ for 4 hours to obtain plastic granules.
[0066] Step 4: Injection molding. The dried plastic granules are injection molded into standard samples using an injection molding machine. The injection temperature is 220°C for all sections of the barrel, 40°C for the mold, 70 MPa for the injection pressure, 40 MPa for the holding pressure, and 20s for the cooling time.
[0067] Comparative Example 2: This comparative example provides a production process for plastic granules. The difference from Example 1 is that this comparative example does not add nano-calcium carbonate that has undergone stearic acid surface activation treatment.
[0068] 100 parts of recycled polypropylene (MFR 20 g / 10min, 230℃ / 2.16kg, obtained from recycled household appliance materials); glycidyl methacrylate grafted polyolefin elastomer (GMA grafting rate 0.5 wt%, MFR 3.5 g / 10min, 190℃ / 2.16kg, density 0.88 g / cm³). 3 10 parts; 5 parts of chopped glass fiber (12 μm in diameter, 4 mm in length, surface-treated with aminosilane coupling agent KH-550); 0.2 parts of α-nucleating agent NA-21 (organoaluminum phosphate salt, white powder); 0.2 parts of antioxidant 1010 (hindered phenolic primary antioxidant); 0.1 parts of antioxidant 168 (phosphite secondary antioxidant); 0.5 parts of zinc stearate (lubricant).
[0069] The preparation process includes the following steps: Step 1: Raw material pretreatment. The recycled polypropylene granules were dried in an 80℃ forced-air drying oven for 4 hours to achieve a moisture content of ≤0.05%; the chopped glass fibers were dried at 110℃ for 2 hours.
[0070] Step 2: Premixing. 100 parts of recycled polypropylene, 10 parts of glycidyl methacrylate-grafted polyolefin elastomer, 0.2 parts of α-nucleating agent NA-21, 0.2 parts of antioxidant 1010, 0.1 parts of antioxidant 168, and 0.5 parts of zinc stearate are mixed in a high-speed mixer at 700 rpm for 4 minutes to ensure uniform distribution of the components, thus obtaining a premix.
[0071] Step 3: Melt Blending Extrusion. A co-rotating twin-screw extruder (L / D ratio L / D = 40) was used. The screw temperatures for each zone were set as follows: Zone 1 170℃, Zone 2 185℃, Zone 3 200℃, Zone 4 210℃, Zone 5 215℃, Zone 6 215℃, Zone 7 210℃, Zone 8 205℃, and Die Head 200℃. The premix obtained in Step 2 was added through the main feed inlet, and the chopped glass fibers were added through the side feed inlets of zones 5-6. The screw speed was 300 rpm. After cooling in a water bath, the extruded strip was granulated. The granules were dried at 80℃ for 4 hours to obtain plastic granules.
[0072] Step 4: Injection molding. The dried plastic granules are injection molded into standard samples using an injection molding machine. The injection temperature is 220°C for all sections of the barrel, 40°C for the mold, 70 MPa for the injection pressure, 40 MPa for the holding pressure, and 20s for the cooling time.
[0073] Comparative Example 3: This comparative example provides a production process for plastic granules. The difference from Example 1 is that this comparative example does not add α-nucleating agent NA-21.
[0074] 100 parts of recycled polypropylene (MFR 20 g / 10min, 230℃ / 2.16kg, obtained from recycled household appliance materials); glycidyl methacrylate grafted polyolefin elastomer (GMA grafting rate 0.5 wt%, MFR 3.5 g / 10min, 190℃ / 2.16kg, density 0.88 g / cm³). 3 10 parts; 8 parts of nano-calcium carbonate (particle size 40 nm, stearic acid treatment amount 2.5 wt%, activation index ≥95%) surface-activated by stearic acid; 5 parts of chopped glass fiber (diameter 12 μm, length 4 mm, surface-treated with aminosilane coupling agent KH-550); 0.2 parts of antioxidant 1010 (hindered phenolic main antioxidant); 0.1 parts of antioxidant 168 (phosphite auxiliary antioxidant); 0.5 parts of zinc stearate (lubricant).
[0075] The preparation process includes the following steps: Step 1: Raw material pretreatment. The recycled polypropylene granules were dried in an 80℃ forced-air drying oven for 4 hours to achieve a moisture content of ≤0.05%; the nano-calcium carbonate treated with stearic acid surface activation was dried at 105℃ for 2 hours; and the chopped glass fibers were dried at 110℃ for 2 hours.
[0076] Step 2: Premixing. 100 parts of recycled polypropylene, 10 parts of glycidyl methacrylate-grafted polyolefin elastomer, 8 parts of nano-calcium carbonate treated with stearic acid surface activation, 0.2 parts of antioxidant 1010, 0.1 parts of antioxidant 168, and 0.5 parts of zinc stearate are mixed in a high-speed mixer at 700 rpm for 4 min to ensure uniform distribution of the components and obtain a premix.
[0077] Step 3: Melt Blending Extrusion. A co-rotating twin-screw extruder (L / D ratio L / D = 40) was used. The screw temperatures for each zone were set as follows: Zone 1 170℃, Zone 2 185℃, Zone 3 200℃, Zone 4 210℃, Zone 5 215℃, Zone 6 215℃, Zone 7 210℃, Zone 8 205℃, and Die Head 200℃. The premix obtained in Step 2 was added through the main feed inlet, and the chopped glass fibers were added through the side feed inlets of zones 5-6. The screw speed was 300 rpm. After cooling in a water bath, the extruded strip was granulated. The granules were dried at 80℃ for 4 hours to obtain plastic granules.
[0078] Step 4: Injection molding. The dried plastic granules are injection molded into standard samples using an injection molding machine. The injection temperature is 220°C for all sections of the barrel, 40°C for the mold, 70 MPa for the injection pressure, 40 MPa for the holding pressure, and 20s for the cooling time.
[0079] Comparative Example 4: This comparative example provides a production process for plastic granules. The difference from Example 1 is that maleic anhydride-grafted polyolefin elastomer is used instead of glycidyl methacrylate-grafted polyolefin elastomer in this comparative example.
[0080] 100 parts of recycled polypropylene (MFR 20 g / 10min, 230℃ / 2.16kg, obtained from recycled household appliance materials); 10 parts of maleic anhydride grafted polyolefin elastomer (MAH grafting rate 0.5 wt%, MFR 3.5 g / 10min, 190℃ / 2.16kg); 8 parts of stearic acid surface-activated nano-calcium carbonate (particle size 40 nm, stearic acid treatment amount 2.5 wt%, activation index ≥95%); 5 parts of chopped glass fiber (diameter 12μm, length 4 mm, surface-treated with aminosilane coupling agent KH-550); 0.2 parts of α-nucleating agent NA-21 (organoaluminum phosphate salt, white powder); 0.2 parts of antioxidant 1010 (hindered phenolic primary antioxidant); 0.1 parts of antioxidant 168 (phosphite secondary antioxidant); 0.5 parts of zinc stearate (lubricant).
[0081] The preparation process includes the following steps: Step 1: Raw material pretreatment. The recycled polypropylene granules were dried in an 80℃ forced-air drying oven for 4 hours to achieve a moisture content of ≤0.05%; the nano-calcium carbonate treated with stearic acid surface activation was dried at 105℃ for 2 hours; and the chopped glass fibers were dried at 110℃ for 2 hours.
[0082] Step 2: Premixing. 100 parts of recycled polypropylene, 10 parts of maleic anhydride-grafted polyolefin elastomer, 8 parts of stearic acid-surface-activated nano-calcium carbonate, 0.2 parts of α-nucleating agent NA-21, 0.2 parts of antioxidant 1010, 0.1 parts of antioxidant 168, and 0.5 parts of zinc stearate are mixed in a high-speed mixer at 700 rpm for 4 minutes to ensure uniform distribution of the components, thus obtaining a premix.
[0083] Step 3: Melt Blending Extrusion. A co-rotating twin-screw extruder (L / D ratio L / D = 40) was used. The screw temperatures for each zone were set as follows: Zone 1 170℃, Zone 2 185℃, Zone 3 200℃, Zone 4 210℃, Zone 5 215℃, Zone 6 215℃, Zone 7 210℃, Zone 8 205℃, and Die Head 200℃. The premix obtained in Step 2 was added through the main feed inlet, and the chopped glass fibers were added through the side feed inlets of zones 5-6. The screw speed was 300 rpm. After cooling in a water bath, the extruded strip was granulated. The granules were dried at 80℃ for 4 hours to obtain plastic granules.
[0084] Step 4: Injection molding. The dried plastic granules are injection molded into standard samples using an injection molding machine. The injection temperature is 220°C for all sections of the barrel, 40°C for the mold, 70 MPa for the injection pressure, 40 MPa for the holding pressure, and 20s for the cooling time.
[0085] Mechanical property testing: Tensile strength and elongation at break were tested according to GB / T 1040.2, using type I dumbbell-shaped specimens, tensile speed 50 mm / min, and test temperature 23±2℃; flexural strength and flexural modulus were tested according to GB / T 9341, with specimen size 80×10×4 mm, bending speed 2 mm / min, span 64 mm, and test temperature 23±2℃; notched impact strength of simply supported beams was tested according to GB / T 1043.1, with specimen size 80×10×4 mm, type A notch, and pendulum energy 4J, and the performance was tested at 23±2℃ and -20±2℃ respectively.
[0086] Table 1. Mechanical property test results of the examples and comparative examples.
[0087] As can be seen from the data in Table 1, the overall mechanical properties of Examples 1-5 are significantly better than those of Comparative Examples 1-4, especially in achieving a "rigid-toughness balance". This is because during the melt blending extrusion process, the polar terminal groups generated by the degradation of recycled polypropylene react chemically with the polyolefin elastomer containing epoxy groups to form strong covalent bonds, achieving reactive compatibilization. This chemical bonding allows the elastomer to be stably dispersed in the matrix as submicron particles, undergoing cavitation and shear yielding upon impact, effectively absorbing impact energy. Simultaneously, the surface-activated nano-inorganic rigid particles provide rigid support in the matrix, inducing crimping and shear yielding under external force, producing a synergistic toughening and strengthening effect with the elastomer. The α-nucleating agent induces the formation of a thermodynamically stable α-crystal form, refining the spherulitic structure, improving the crystallinity and stiffness of the matrix, and avoiding the phase transformation risk of metastable crystal forms during secondary processing, resulting in higher performance stability of the plastic particles.
[0088] Example 1 introduces POE-g-GMA, whose epoxy groups react with the polar terminal groups of RPP to form a strong covalent interface, resulting in refined and stably dispersed elastomer particles that effectively induce crazing and shear yielding upon impact. Simultaneously, activated nano-calcium carbonate provides rigid support and auxiliary toughening, while NA-21-induced α-crystal structure refines the spherulites. These three elements synergistically significantly improve impact strength while maintaining high modulus. In contrast, the comparative example lacks these key elements, resulting in weak interfacial bonding or coarse crystal structures, leading to low stress transfer efficiency or high brittleness.
[0089] Comparative Example 1 used ordinary POE, lacking reactive compatibilization. The elastomer and matrix relied solely on physical compatibility, leading to easy interface debonding. Its impact strength was significantly lower than Example 1, and the flexural modulus was also reduced due to interface defects. Comparative Example 2 did not add nano-calcium carbonate, lacking the rigid particles' initiation of crazing and the refinement and restriction of spherulites, resulting in significant losses in both impact strength and modulus. Comparative Example 3 did not add an α-nucleating agent, resulting in lower matrix crystallinity and coarser spherulites, leading to a significant decrease in flexural modulus and a reduction in impact strength. Comparative Example 4 used MAH-grafted elastomer instead of GMA. Because MAH's reactivity with the carboxyl and hydroxyl groups generated from RPP degradation is weaker than that of the epoxy groups in GMA, the reactive compatibilization effect was insufficient, and its impact strength and modulus were lower than Example 1.
[0090] Example 6 used calcium carbonate with two different modification methods, and its overall performance was further improved compared to Example 1. This is because the vinyl groups on the surface of KH-570-treated calcium carbonate endow it with lower surface energy and reactivity with the GMA groups of the elastomer. During melt blending, it preferentially migrates to the elastomer-matrix interface or the interior of the elastomer phase, and upon impact, it induces crazes and synergistic energy absorption simultaneously with elastomer cavitation. The nonpolar long chains on the surface of stearic acid-treated CaCO3 endow it with good compatibility with the PP matrix, stably dispersed in the matrix, providing rigid support and independent craze toughening. The two different treatments of calcium carbonate not only further improved the toughness of the material but also increased its rigidity.
[0091] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0092] The embodiments described above are merely illustrative of several implementation methods of this application, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of this application, and these all fall within the protection scope of this application. Therefore, the protection scope of this patent application should be determined by the appended claims.
Claims
1. A production process for high-performance plastic granules, characterized in that, Includes the following steps: Recycled polypropylene, polyolefin elastomer containing epoxy groups, surface-activated nano-inorganic rigid particles, and α-nucleating agent are mixed to obtain a premix. The premixed material is melt-blended and extruded, then cooled and pelletized to obtain plastic granules.
2. The production process according to claim 1, characterized in that, The epoxy group-containing polyolefin elastomer is a glycidyl methacrylate-grafted polyolefin elastomer, and the glycidyl methacrylate grafting rate is 0.5%-1wt%.
3. The production process according to claim 1, characterized in that, The surface-activated nano-inorganic rigid particles are stearic acid-activated nano-calcium carbonate with a particle size of 30-80 nm.
4. The production process according to claim 1, characterized in that, The α-nucleating agent is an organophosphate nucleating agent.
5. The production process according to claim 1, characterized in that, The production process also includes chopped glass fibers.
6. The production process according to claim 5, characterized in that, In the melt blending extrusion step, the chopped glass fibers are added from the side feed port of the extruder.
7. The production process according to claim 5, characterized in that, The chopped glass fiber comprises 3-15 parts per 100 parts by weight of recycled polypropylene.
8. The production process according to claim 1, characterized in that, Based on 100 parts by weight of recycled polypropylene, the polyolefin elastomer containing epoxy groups comprises 5-15 parts, the surface-activated nano-inorganic rigid particles comprise 3-15 parts, and the α-nucleating agent comprises 0.2-0.3 parts.
9. The production process according to claim 1, characterized in that, The temperature of the melt blending extrusion is 170-240℃.
10. A high-performance plastic granule, characterized in that, It is prepared using the production process described in any one of claims 1-9.